Measuring technical and water use efficiency and their determinants for wheat production in Faisalabad, Pakistan - Gill, Moeed Waqar (2015)
Pakistan is confronting one of the most striking challenges of water scarcity in the world. In Pakistan, per capita consumption of water is about 1038 m3 and 90% of agricultural production comes from irrigated lands. Total agriculture land of Faisalabad is 584,495.14 hectares and the total irrigated land is 465,604 hectares. The main objective of the study is to evaluate the technical and water use efficiency to increase wheat productivity in Faisalabad District, Pakistan. This study has also recognized a variety of socioeconomic and wheat farm related factors responsible for technical, allocative and economic inefficiency. The study used DEA (Data Envelopment Analysis) approach to estimate the technical efficiency and Tobit regression model was used to discover factors responsible for technical inefficiency. A total of 180 farmers were selected and face to face interviewed was carried out in the District of Faisalabad. A tabular study was undertaken to find out different farm particular characteristics of the three farm size categories, i.e. small farmers, medium farmers and large farmers. The average farm size of the small, medium and large farmers was found to be 3 acres, 9 acres and 28 acres, respectively. The average application of fertilizers by all categories was found to be two bags of urea and one bag of DAP (Diammonium Phosphate) and an average of 2 trolleys of FYM (Farmyard Manure) for one acre of field. According to the study, the result shows that large farmers are more efficient than medium farmers and small farmers are least efficient. Small farms overall and water T.E in CRS are 0.75 and 0.67 and in VRS are 0.92 and 0.80 respectively. Medium farms overall and water T.E in CRS are 0.85 and 0.75 and in VRS are 0.93 and 0.85 respectively. Large farms overall and water T.E in CRS are 0.89 and 0.73 and in VRS are 0.95 and 0.87 respectively. Furthermore, the higher education level of large farmers was also crucial against the low yields of small and medium farmers. Especially small farmers are performing low due to unavailability of sufficient information about changing practices and the new improvement in the sector. Family size and Education are the significance variables. Many farmers are either uninformed of the credit ease of use or else; due to high interest rate they were not ready to take a loan. Small and some medium farmers appeared to use their family labor in the agricultural practices. Small farmers do not have sources of income other than farming. But few medium sized farmers were identified with income from other sources. But mostly large farmers have their sources of income other than farming. This problem has not given the due significance by the agricultural extension workers, as they do not visit the farmers habitually.